Fundamentals of anatomy & physiology - Rizzo, Donald C. (Thomson/Delmar Learning, 2006)
Designed for allied health learners with little or no biology knowledge, this full-color book is a comprehensive introduction to anatomy & physiology. It is organized according to body systems, and focuses on the body working together to promote homeostasis. Chapters are self-contained so instructors can teach in any order preferred. Essential laboratory exercises included at the end of chapters provide hands-on lab experience. Key terms with phonetic pronunciations help build vocabulary. Free interactive CD-ROM encourages mastery of content through quizzes, games, and animations.